Point-Counterpoint Strategy for Better Reading Comprehension on EFL Junior High School Students - Rizal Arisman; Triyulan Safitrih (UIR Press, 2023)
Point-Counterpoint is one of the strategies that can be used to stimulate students and make them free in reading. This study is conducted to reveal the significant difference in reading ability under Point-Counterpoint strategy and conventional technique in class seven students at SMP Negeri 1 Batauga, South Buton regency. The design of this study was a quasi-experimental method. The sample was taken using cluster sampling, in which took class VII-F was selected as an experimental group and class VII-E was a control group. The instruments used were a pretest and a posttest. The results revealed that the average score for the pretest in the experimental group was 47.83, while the average score in the control group was 34.77. The average score for the posttest in the experimental group was 71.13, while it was 58.62 in the control group. Those scores indicated that the students had good reading ability in the experimental group, while the students in the control group had moderate comprehension in reading. The requirement testing outcome informed that the data had a normal distribution and were homogeneous. The hypothesis testing indicated that the tcount was 4.489 and the significant score was 0.000. Both results meant that the Point-Counterpoint strategy was significantly different from a conventional method toward students’ reading comprehension.